Boys with Internalizing and Externalizing Behavior Problems: A Case Control Study - Bolsoni-Silva,Alessandra Turini (2019)
Abstract The simultaneous occurrence of internalizing and externalizing behavior problems characterizes a risk to the child’s development in clinical terms and requires more studies. The objective was to correlate, from the evaluation of the biological mothers, child social skills, resources of the family environment and parenting practices for a group of boys who presented both internalizing and externalizing behavior problems, in comparison to a paired group of children without behavior problems. A case-control design was adopted, with 36 biological mothers of boys who were distributed in two groups, G1 - 18 boys identified with behavior problems (clinical) and G2 - 18 boys identified without behavior problems (nonclinical). The mothers completed instruments regarding parental practices, environment resources and child behaviors. In the clinical group, a significantly greater use of negative practices (especially “hitting”) was identified, as well as a deficit of positive practices and a lack of resources of the family environment. Correlations showed that, in the nonclinical group, positive practices were associated with skilled behaviors, whereas negative practices were associated with problem behaviors - although this did not happened in the clinical group. This suggests a lack of consistence in the application of these practices in this group. These data contribute to planning guidance practices for parents.